High Altitude Sports Training Complex
The High Altitude Sports Trainng Center (HASTC) with the ideal base elevation of 2,134 meters offers a wide variety of training amenities to domestic and international athletes and teams. The typical users of the High Altitude Sports Training Complex are elite, Olympic, or amateur athletes who are interested in making significant improvements in their competitive performance. The High Altitude Sports Training Complex has a number of excellent facilities at its disposal, allowing the accommodation of virtually any sport, e.g. the Wall Aquatic Cente, the Lumberjack Stadium Track, the climate-controlled Walkup Skydome, the USA weightlifting Federation Regional Training Center or the recreation center. HASTC offers also a wide range of support services (research, medical care, ...).